Pre Existing Condition Regulation in Indonesian Life Insurance Policies: Pengaturan Pre Existing Condition dalam Polis Asuransi Jiwa di Indonesia - Euginia Nataniela Awuy; Ariawan Gunadi (Universitas Muhammadiyah Sidoarjo, 2026)
Background: Life insurance plays a crucial role in balancing financial protection and risk management, where pre-existing condition clauses function to maintain fairness between premium payments and actual risks borne by insurers. Specific Background: In Indonesia, the implementation of these clauses often triggers disputes due to inconsistent interpretations, lack of regulatory standardization, and low public literacy regarding insurance contracts. Knowledge Gap: Despite their importance, limited studies examine how effectively these clauses mitigate risk while maintaining legal certainty amid regulatory ambiguity and practical challenges in underwriting and proof. Aim: This study evaluates the effectiveness of pre-existing condition clauses as a risk-mitigation mechanism for Indonesian life insurance companies. Results: Findings show that these clauses prevent adverse selection, strengthen utmost good faith, and support accurate underwriting, though effectiveness is hindered by unclear definitions, uneven documentation, agent miscommunication, and difficulties in proving prior illnesses. Novelty: This research integrates legal, technical, and consumer-protection perspectives to identify systemic weaknesses that reduce clause enforceability. Implications: Strengthening regulatory standards, improving transparency, and enhancing underwriting systems are essential to reduce disputes and reinforce legal certainty in life insurance governance. Highlights: Evaluates how pre-existing condition clauses function as a core risk-mitigation tool in Indonesian life insurance. Highlights legal and practical challenges, including regulatory gaps, proof difficulties, and low insurance literacy. Recommends strengthening regulation, transparency, and underwriting systems to reduce disputes and enhance legal certainty. Keywords: Pre-Existing Condition, Life Insurance, Risk Mitigation, Legal Certainty, Underwriting